The relationship between halal and technology, an approach to consider Halal techniques in the robot revolution and artificial intelligence / Ahmed S. Ahmed and Muhammad Laeba - Ahmed, Ahmed S.; Laeba, Muhammad (Academy of Contemporary Islamic Studies (ACIS), 2018)
The relationship between technology and Halal has existed since the Halal concept linked with the industry and the production by the halal products. This marriage increasing dramatically with the technological developments, especially through robotics and artificial intelligence, which led the researcher to highlight this relationship and employing it supporting the Halal sector. To strengthen this relationship the researcher has back to the beginning of it that was in the auto slaughtering and has shown the gap that made by the technology and its effect on halal standards, which was due to the unconsidered the principles of halal in the technology which has made already in the auto slaughtering, that led the researcher to discover the relationship's features between robot development and halal techniques, and supports this relationship to guarantee the Islamic principle in halal products and be away from the Islamic justification to the technology.